2006
DOI: 10.1088/0967-3334/27/5/s20
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of the shape of conductivity spectra using differential multi-frequency magnetic induction tomography

Abstract: Magnetic induction tomography (MIT) of biological tissue is used for the reconstruction of the complex conductivity distribution κ inside the object under investigation. It is based on the perturbation of an alternating magnetic field caused by the object and can be used in all applications of electrical impedance tomography (EIT) such as functional lung monitoring and assessment of tissue fluids. In contrast to EIT, MIT does not require electrodes and magnetic fields can also penetrate non-conducting barriers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 9 publications
0
26
0
Order By: Relevance
“…6) should be nearly symmetric but due to different vibration dynamics of different coils the symmetry is not perfect. The achieved system performance is sufficient for low contrast conductivity imaging such as in [8].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6) should be nearly symmetric but due to different vibration dynamics of different coils the symmetry is not perfect. The achieved system performance is sufficient for low contrast conductivity imaging such as in [8].…”
Section: Discussionmentioning
confidence: 97%
“…We have developed a fast parallel multi-frequency imaging system which operates from 50 kHz to 1 MHz [7]. It comprises 16 RXC and 16 TXC and allows frequency differential imaging [8], whereas 8+8 coils can be operated in single shot mode. However, due to the the low sensitivity vibrations and thermal drifts cause significant errors [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of additional interest is frequency difference imaging, which could be useful if the test subjects show different responses to frequency variation. The reconstruction of pathophysiological information using multi-frequency data and frequency dependence sensitivity matrix was studied in [46], which showed that low resolution similar to those obtained from electrical impedance tomography is possible.…”
Section: Multi-frequency Operationmentioning
confidence: 99%
“…Magnetic induction tomography is a non-contact technique, in contrast to widely studied electrical impedance tomography [33]. Another advantage of MIT is its explicit frequency dependence, which allows for more accurate reconstruction of the body properties [34].…”
Section: Magnetic Induction Tomographymentioning
confidence: 99%
“…where the function A is the solution of the problem (34) for any e ∈ L 2 (Γ) and ω > 0 fixed, is a well-defined and strongly continuous map from the set…”
Section: Forward Problemmentioning
confidence: 99%